New apartments under construction in Yellowknife ... - Campbell, Sandy (University of Alberta Library, 2015)
Yellowknife is expanding. This construction site is on the west side of the City. In the right foreground there is rubble created by blasting the shield rock to create a more even surface upon which to build. ...